Verification of pure moment testing in a multi–degree of freedom spine testing apparatus - Fuller, Amy M. (Int J Spine Surg, 2012)
BACKGROUND: Pure moment testing is a common method used in cadaveric spine testing. The fundamental basis for the widespread acceptance of applying a pure moment is uniform loading along the column of the spine. To our knowledge, this protocol has not been experimentally verified on a multi–degree of freedom testing apparatus. Given its ubiquitous use in spine biomechanics laboratories, confirmation of this comparative cadaveric test protocol is paramount. METHODS: Group A specimens (n =13) were used to test the pure moment protocol, by use of 3 constructs that changed the number of involved vertebrae, orientation, and rigidity of the spine construct. Group B specimens (n = 6) were used to determine whether potting orientation, testing order, or degradation affected the range of motion (ROM) by use of 8 constructs. Each group was subjected to 3 cycles of flexion-extension, lateral bending, and axial torsion. The data from the third cycle were used to calculate the ROM for each method. RESULTS: Group A testing resulted in significant differences in ROM across the 3 constructs for lateral bending and axial torsion (P < .02) and trended toward a difference for flexion-extension (P = .055). Group B testing showed an increase in ROM across 8 constructs (P < .04) but no significant difference due to the orientation change. CONCLUSION: The increased ROM across constructs observed in both groups indicates that the cause is likely the testing order or degradation of the specimens, with orientation having no observed effect. The data do not invalidate pure moment testing, and its use should persist.